Die Vergangenheitsbewältigung als eine Vorbedingung für die Transformation – Der Fall Mazedoniens - Spasov, Aleksandar Lj. (Deutsche Stiftung für Internationale rechtliche Zusammenarbeit (IRZ), Südosteuropa Geselschaft (SOG), 2019)
Coming to terms with the past as a precondition for transformation – the case of Macedonia Summary In order to have successful democratic transition and achieve effective transformation, states should not only define and implement values and rules of conduct for the future, but, furthermore, they should find appropriate and acceptable explanations of the events that occurred in the past. Macedonia had an unsuccessful process of dealing with its own authoritarian past. During the first decade of the independence, dealing with the past was avoided as a task. Avoiding dealing with the past had a boomerang effect in the years after the change of the social-democratic with the national conservative government in 2006. The new government, using the failures of all previous governments, used this flaw of the new democratic legal and political order for its own political interest and abused the late lustration for personal attacks on its political opponents. Parallel to the lack of dealing with the authoritarian past, the Macedonian legal system faced gradual change of its continental legal tradition by unreasonable and unjustified introduction of legal implants from other legal traditions opposed to the principles of the continental legal tradition during the past two and a half decades. This created additional problems in the transformation process. The “new beginning” declared by the new government after the government change in 2017, will be possible only if the final goals of the reforms will be laws which are not a product of personal or clanbased interests and if a policy of non-selective application of the laws is established. In addition, it is necessary that in judiciary the judge posts will be occupied by the most capable jurists having also high personal and moral integrity.